Generative AI: Opportunities, risks and implications for Financial Services - Ravikumar Mani Naidu Gunasekaran (The Eastasouth Journal of Information System and Computer Science, 2024)
Generative Artificial Intelligence (GenAI) is rapidly transforming the financial services industry by enabling advanced automation, intelligent decision-making, and enhanced customer experiences. Technologies such as large language models and generative models are reshaping processes across risk management, fraud detection, regulatory reporting, and customer engagement. However, the adoption of GenAI introduces significant challenges, including model risks, data privacy concerns, regulatory uncertainties, and ethical implications. This paper explores the opportunities and risks associated with generative AI in financial services and proposes a structured framework for responsible adoption. By integrating governance, risk management, and regulatory compliance mechanisms, the study provides practical insights for financial institutions seeking to leverage GenAI while ensuring security, transparency, and resilience.